Familial papular epidermal nevus with "skyline" basal cell layer and multiple pilomatricomas: A new association?. Issue 3 (28th February 2018) - Rizzoli, Laura; Balestri, Riccardo; Rech, Giulia; Zorzi, Maria Grazia; Speziali, Luigi; Pedrolli, Annalisa; Girardelli, Carlo Renè
Abstract: Papular epidermal nevus with "skyline" basal cell layer is a newly described keratinocytic nevus. Recently, papular epidermal nevus with "skyline" basal cell layer has been reported in association with extracutaneous involvement, and the term papular epidermal nevus with "skyline" basal cell layer syndrome is used to indicate a neurocutaneous syndrome characterized by the presence of papular epidermal nevus with "skyline" basal cell layer and different neurologic symptoms that seem to improve during infancy and adolescence. Multiple pilomatricomas have been reported in association with various syndromes. We report herein papular epidermal nevus with "skyline" basal cell layer associated with multiple pilomatricomas in two members of a family with the aim of drawing attention to this peculiar epidermal nevus to improve our knowledge of the syndrome.